2004
DOI: 10.1128/jvi.78.11.5875-5882.2004
|View full text |Cite
|
Sign up to set email alerts
|

The NV Gene of Snakehead Rhabdovirus (SHRV) Is Not Required for Pathogenesis, and a Heterologous Glycoprotein Can Be Incorporated into the SHRV Envelope

Abstract: Snakehead rhabdovirus (SHRV) affects warm-water fish in Southeast Asia and belongs to the genus Novirhabdovirus by virtue of its "nonvirion" (NV) gene. To examine the function of the NV gene, we used a recently developed reverse genetic system to produce a viable recombinant SHRV carrying an NV gene deletion. The recombinant virus was produced at the same rate and same final concentrations as the wild-type virus in cultured fish cells in spite of the NV gene deletion. The role of the NV protein in fish pathoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
1
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 20 publications
1
26
1
2
Order By: Relevance
“…Thus, rVHSV-⌬NV appears to be as attenuated as previously described for rIHNV-⌬NV, confirming the essential role of the NV protein of salmonid novirhabdovirus. In contrast to our findings, Alonso et al, using a reverse-genetic system established with snakehead rhabdovirus (SHRV), a warm-water fish novirhabdovirus, have observed no apparent role of the NV protein in replication in vitro as well as in fish pathogenesis (1). It could be of interest to replace the VHSV and IHNV NV genes with that of SHRV to evaluate the potential of the complementation of this NV protein on both virus phenotypes and thus evaluate whether these three NV proteins that share less than 30% of homology have a common function.…”
Section: Discussioncontrasting
confidence: 54%
“…Thus, rVHSV-⌬NV appears to be as attenuated as previously described for rIHNV-⌬NV, confirming the essential role of the NV protein of salmonid novirhabdovirus. In contrast to our findings, Alonso et al, using a reverse-genetic system established with snakehead rhabdovirus (SHRV), a warm-water fish novirhabdovirus, have observed no apparent role of the NV protein in replication in vitro as well as in fish pathogenesis (1). It could be of interest to replace the VHSV and IHNV NV genes with that of SHRV to evaluate the potential of the complementation of this NV protein on both virus phenotypes and thus evaluate whether these three NV proteins that share less than 30% of homology have a common function.…”
Section: Discussioncontrasting
confidence: 54%
“…In addition to SE-SVA-1033, isolate DK-5e59 was the only remaining isolate to encode a Phe at this point mutation. Due to the relatively small size of the viral genome (approximately 11 000 nt), Alonso et al (2004) postulated the NV gene (369 nt) must have an important role in viral replication, although it was not essential for pathogenesis in snakehead rhabdovirus (SHRV). However, Thoulouze et al (2004) showed the gene to be essential for pathogenicity of another salmonid rhabdovirus, infectious haematopoietic necrosis virus (IHNV), whereby removal of the NV gene significantly reduced the virulence of the virus for rainbow trout, as also demonstrated by Brémont (2005).…”
Section: Discussionmentioning
confidence: 99%
“…VHSV is a rhabdovirus comprised of a single-stranded RNA genome encoding nucleo-(N), phospho-(P), matrix-(M), glyco-(G) and RNA-dependent (L) polymerase structural proteins. Classified within the genus Novirhabdoviridae, VHSV also encodes a characteristic non-structural (non-virion, NV) protein, situated between the G and L genes, the functional role of which remains uncertain (Alonso et al 2004. Four main genotypes of the virus have been identified which are independent of the genomic region used for analysis (EinerJensen et al 2004) and are restricted to 4 broadly distinct geographical locations (Snow et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Natural SHRV infection has only been associated with the complex disease EUS; however, experimental infection with SHRV has been successful in snakehead fry and juveniles and in zebrafish (2,12,21,29). This is the first study to examine, in detail, the pathogenesis and antiviral response in zebrafish associated with SHRV infection.…”
Section: Discussionmentioning
confidence: 99%
“…Zebrafish infected with SVCV exhibited significant mortalities and histopathology, marked by necrosis of the gills, liver, and spleen. In a recent collaboration between our lab and the Leong lab (2), recombinant SHRV mutants were used to demonstrate the role of the SHRV nonvirion gene during infection in adult zebrafish; however, detailed pathogenesis and antiviral response were not reported.…”
mentioning
confidence: 99%